Activism in southeast Asian ethnomusicology - Tan, Sooi Beng (Muzikološki zbornik, 2008)
Beginning with a short overview of the strategies and activities in applied ethnomusicology in Southeast Asia, this paper focuses on the development of a socially engaged approach to empower young people in Malaysia to address two concerns: revitalizing traditions and bridging cultural barriers in a multiethnic and multireligious society where tensions often occur.
Keywords: etnomuzikologija; glasba; identiteta; multikulturalnost; music; procesualno gledališče; tradicija; tradition; umetnostna vzgoja